Chronic treatment with enhancer drugs modifies the gene expression of selected parameters related to brain plasticity in rats under stress conditions. (October 2022) - Hrivikova, K.; Zelena, D.; Graban, J.; Puhova, A.; Miklya, I.; Balazsfi, D.; Jezova, D.
Abstract: Selegiline, also known as L-deprenyl, and (2 R )-1-(1-benzofuran-2-yl)- N -propylpentane-2-amine (BPAP) were found to induce enhancement of monoamine neurotransmission in low and very low doses. In addition, these enhancers may modify glutamatergic neurotransmission. The aim of the present study was to test the hypothesis that under stress conditions, chronic treatment with enhancer drugs has a positive impact on the glutamatergic system and other parameters related to brain plasticity, stress-related systems, and anxiety behavior. We exposed male Wistar rats to a chronic mild stress procedure combined with chronic treatment with two synthetic enhancer drugs. The gene expression of GluR1, an AMPA receptor subunit was reduced by repeated treatment with deprenyl in the hippocampus and with both BPAP and deprenyl in the prefrontal cortex. A significant reduction of NMDA receptor subunit GluN2B expression was observed in the hippocampus but not in the prefrontal cortex. Deprenyl treatment led to an enhancement of hippocampal BDNFmRNA concentrations in stress-exposed rats. Treatment with enhancer drugs failed to induce significant changes in stress hormone concentrations or anxiety behavior. In conclusion, the present study in chronically stressed rats showed that concomitant treatment with enhancer drugs did not provoke substantial neuroendocrine changes, but modified gene expression of selected parameters associated with brain plasticity. Observed changes may indicate a positive influence of enhancer drugs on brain plasticity, which is important for preventing negative consequences of chronic stress and enhancement of stress resilience. It may be suggested that the changes in glutamate receptor subunits induced by enhancer drugs are brain region-specific and not dose-related. Highlights: Under stress conditions, enhancers modify parameters related to brain plasticity. Enhancers affect glutamatergic system by reducing GluR1 and GluN2B gene expression. Enhancers increase the gene expression of BDNF in the hippocampus. Enhancers do not modify anxiety behavior and stress hormone release.